Treatment gaps in epilepsy - Pellinen, Jacob (Frontiers in Epidemiology, 2022)
Over 50 million people around the world have epilepsy, and yet, epilepsy recognition and access to care are ongoing issues. Nearly 80% of people with epilepsy live in low-and middle-income countries and face the greatest barriers to quality care. However, there are substantial disparities in care within different communities in high-income countries as well. Across the world, under-recognition of seizures continues to be an issue, leading to diagnostic and treatment delays. This stems from issues surrounding stigma, public education, basic access to care, as well as healthcare worker education. In different regions, people may face language barriers, economic barriers, and technological barriers to timely diagnosis and treatment. Even once diagnosed, people with epilepsy often face gaps in optimal seizure control with the use of antiseizure medications. Additionally, nearly one-third of people with epilepsy may be candidates for epilepsy surgery, and many either do not have access to surgical centers or are not referred for surgical evaluation. Even those who do often experience delays in care. The purpose of this review is to highlight barriers to care for people with epilepsy, including issues surrounding seizure recognition, diagnosis of epilepsy, and the initiation and optimization of treatment.